Exciton Dissociation on Double Z‐scheme Heterojunction for Photocatalytic Application. Issue 26 (8th July 2021) - Shende, Ashok G.; Bhoyar, Toshali; Vidyasagar, Devthade; Singh, Jaspreet; Kosankar, Prakash T.; Umare, Suresh S.
Abstract: Constructing heterojunction is one of the promising approaches to obtain desired photocatalysts with enhanced photocatalytic activity. Herein, we have fabricated a Fe2 O3 ‐PrFeO3 /g‐C3 N4 ternary heterostructure by a simple wet chemical method to improve the photocatalytic activity of pristine g‐C3 N4 . The as‐prepared catalyst has shown 7.8 times higher photocatalytic degradation of dye acid violet 7 and generated 379.29 μmolL −1  h −1 of ammonia under visible‐light irradiation. The ternary heterojunction was found to form a double Z‐scheme heterojunction that facilitates interfacial electron transfer, promotes the separation of photogenerated charge carriers, and also enhances light harvesting property. The enhanced photocatalytic performance of the catalyst is ascribed to the formation of double Z‐scheme heterojunction, which offers low charge transfer resistance thereby lowering the recombination of photoexcitons and increasing the lifetime of photoexcitons. Abstract : In this work, a Fe2 O3 ‐PrFeO3 /g‐C3 N4 ternary heterojunction was fabricated to improve the photocatalytic efficiency of pristine g‐C3 N4 . The ternary heterojunction exhibits extended optical response and facilitates effective separation of photoexciting via double Z‐scheme electron transport improving the lifetime of photoexcitons. As a result, under visible‐light illumination, the catalyst demonstrated enhanced photocatalytic degradation of AV7 dye and nitrogen fixation activity.